1996
DOI: 10.1002/(sici)1097-0215(19960315)65:6<768::aid-ijc10>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Can papilloma virus testing be used to improve cervical cancer screening?

Abstract: This report investigates different options for using human papillomavirus (HPV) testing in cervical cancer prevention. These options are evaluated by a stochastic model of the progression of pre-malignancy and its relationship to HPV infection. Three screening policies are compared: 2 based on cytological screening, with or without HPV testing, and I in which HPV testing is the primary screening method. A policy of HPV testing for women with mildly abnormal smears would have little effect on the overall incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 20 publications
2
29
0
2
Order By: Relevance
“…There is a long history of modelling in cervical cancer (SherlawJohnson et al, 1994(SherlawJohnson et al, , 1999Jenkins et al, 1996;Karnon et al, 2004;Sherlaw-Johnson and Philips, 2004), and studies in the US (Kulasingham and Myers, 2003;Goldie et al, 2004;Taira et al, 2004) have found that HPV vaccination with screening is costeffective. There have been no published analyses of HPV vaccination in the UK, where cervical disease and screening differs from the US.…”
supporting
confidence: 62%
“…There is a long history of modelling in cervical cancer (SherlawJohnson et al, 1994(SherlawJohnson et al, , 1999Jenkins et al, 1996;Karnon et al, 2004;Sherlaw-Johnson and Philips, 2004), and studies in the US (Kulasingham and Myers, 2003;Goldie et al, 2004;Taira et al, 2004) have found that HPV vaccination with screening is costeffective. There have been no published analyses of HPV vaccination in the UK, where cervical disease and screening differs from the US.…”
supporting
confidence: 62%
“…In addition, prospective epidemiologic studies show that the risk of subsequent cervical intraepithelial neoplasia seems to be proportional to the number of specimens testing positive for HPV [9,10], which suggests that only persistent infections may trigger carcinogenic development. Given that there is now considerable interest in the possibility of using HPV testing as a potential cervical cancer screening tool [11][12][13], it is imperative that issues related to viral persistence be addressed by epidemiologic studies. Research on the epidemiology of viral persistence and of its determinants will help in the future formulation of algorithms and policies for inclusion of HPV testing in cervical cancer prevention.…”
mentioning
confidence: 99%
“…While a handful of analyses have examined costs in relation to HPV DNA testing, these analyses have been limited by lack of detailed cost estimates, extreme assumptions regarding the length of progression from HPV infection to clinical disease, or limited use of HPV testing [63][64][65]. One recently published report examined models with different assumptions and concluded that the use of HPV DNA testing could potentially be a cost-effective adjunct to cytology if it allowed for extension of the screening interval [12••].…”
Section: Cost Effectiveness Of Hpv Testing In Cervical Cancer Controlmentioning
confidence: 99%